2022
DOI: 10.1159/000524337
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Delivery and Incidence of Bronchopulmonary Dysplasia: Results from the Population-Based EPICE Cohort

Abstract: <b><i>Introduction:</i></b> Bronchopulmonary dysplasia (BPD) represents a tremendous disease burden following preterm birth. The strong association between compromised gas exchange after birth and BPD demands particular focus on the perinatal period. The mode of delivery can impact on lung fluid clearance and microbial colonization, but its impact on BPD and potential trade-off effects between death and BPD are not established. <b><i>Methods:</i></b> A total of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The infants less than 32 gestational weeks (GW) were still faced with high risk of developing BPD. 1 , 2 , 25 , 26 , 27 The incidence of BPD was 29.2% reported by Chinese Neonatal Network, 25.9% reported by US Vermont Oxford Network, and around 20% reported by Effective Perinatal Intensive Care In Europe (EPICE) cohort. 25 , 26 , 27 A recent study on trends in outcomes for neonates born very preterm in high-income countries showed the BPD incidence was increasing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The infants less than 32 gestational weeks (GW) were still faced with high risk of developing BPD. 1 , 2 , 25 , 26 , 27 The incidence of BPD was 29.2% reported by Chinese Neonatal Network, 25.9% reported by US Vermont Oxford Network, and around 20% reported by Effective Perinatal Intensive Care In Europe (EPICE) cohort. 25 , 26 , 27 A recent study on trends in outcomes for neonates born very preterm in high-income countries showed the BPD incidence was increasing.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 25 , 26 , 27 The incidence of BPD was 29.2% reported by Chinese Neonatal Network, 25.9% reported by US Vermont Oxford Network, and around 20% reported by Effective Perinatal Intensive Care In Europe (EPICE) cohort. 25 , 26 , 27 A recent study on trends in outcomes for neonates born very preterm in high-income countries showed the BPD incidence was increasing. 28 BPD was still the major and severe complication affecting a wide population of very preterm infants, which was found to be a crucial factor for adverse neurodevelopmental outcome of very preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…We constructed 4 models: (1) no adjustments except for country as a fixed effect (termed unadjusted), (2) adjustments for country and additionally on sociodemographic factors, (3) adjustments for country and sociodemographic factors from models 1 and 2 plus adjustment on perinatal factors, and (4) a full model with adjustments for country, sociodemographic factors, JAMA Network Open | Pediatrics perinatal factors, and additionally on severe neonatal morbidities to take into consideration postnatal factors. 23,[26][27][28][29] To avoid collinearity in adjusted models, we included maternal age, education, and country of birth as sociodemographic factors; gestational age, SGA, child sex, and multiplicity as perinatal factors; and a composite of severe morbidity and BPD as neonatal factors. We applied inverse probability weighting (IPW) to account for loss to follow-up as done previously on this population.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy and neonatal variables included single or multiple pregnancy; sex; small for gestational age status, classified as birthweight less than the third, third to ninth, and tenth or greater percentile of intrauterine references developed for the cohort; premature rupture of membranes more than 12 hours before the onset of labor; and antenatal steroid administration (at least 1 dose before delivery irrespective of the time interval to delivery). The following severe neonatal morbidities were considered in analyses as done previously in this cohort: IVH grade III and IV, CPVL, or both; retinopathy of prematurity of stage 3 or greater; necrotizing enterocolitis requiring surgical therapy or peritoneal drainage; and moderate and severe bronchopulmonary dysplasia with ongoing need for respiratory support, supplemental oxygen, or both at 36 weeks …”
Section: Methodsmentioning
confidence: 99%
“…The healthcare of EPIs was drastically optimized during the last decades, including antenatal steroids to promote lung maturity, exogenous surfactant to alleviate respiratory distress syndrome, non-invasive ventilation to reduce volume- and barotrauma of the immature lung, caffeine to improve pulmonary outcome in the short-term and neurodevelopment in the long-term, vitamin A supplementation and early adequate caloric intake to support pulmonary development, as well as the integration of non-medical interventions (e.g., family-centered care) [ 8 , 9 , 10 , 11 , 12 , 13 ]. However, the incidence of BPD remains high and was not significantly improved in the last two decades [ 14 , 15 , 16 ]. It has been increasingly recognized that failure to reduce BPD is likely attributed to its multifactorial origin, and the impact of adverse factors in the antenatal period may be difficult to avoid and remain insufficiently tackled [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%